THE INFLUENCE OF PLAYING BALL TOWARD MOVEMENT ACTIVITY ABILITY TO HYPOACTIVE AUTISM CHILDREN - Anggawati Imanniyah (STIKes MERCUBAKTIJAYA, 2019)
Hypoactive autism children were indicated by slow motoric activity so that it caused the children difficult to move. The children tended passive and they did not have any interest to do movement activity and preferred alone when they looked their friends playing. To help hypoactive autism children in enhancing movement activity ability it required a game which attracted the children’s interest to move i.e. through playing game. The purpose of this research was to analyze movement activity ability before and after giving intervention using playing ball (passing and shooting), with time allocation 10 times meeting and 8 times intervention. This research used quantitative approach with the one group pretest posttest design. The subjects were 5 hypoactive autism children. For data analysis this research used statistic non parametric formula of sign test kind and the method of data collection applied observation and test. From the research result which was then analyzed by using sign test formula, it was obtained that the value of Z counting 1,78 while the value of Z table with critic value 5% one side test was obtained 1,64 so that Z counting 1,78 was greater than Z table1,64 it meant that null hypothesis (Ho) was refused and work hypothesis (Ha) was accepted. In this way it could be concluded that playing ball influenced toward movement activity ability of hypoactive autism children